1992
DOI: 10.1080/03079459208418840
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous leukosis viral antigen in eggs from meat‐type chickens on an avian leukosis virus eradication programme

Abstract: SUMMARYIn an effort to eliminate exogenous avian leukosis virus (ALV) from a susceptible population, albumen of one egg per hen from each of four generations was tested by ELISA for groupspecific antigen (gsa) of leukosis/sarcoma viruses. From 1510 to 2099 hens were tested in each generation. Hens were not used as breeders if optical density readings for gsa were 0.4 or greater. Despite this procedure, there was no appeciable change in the occurrence of gsa in eggs from one generation to the next and in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…In additional case studies of Smith (1987) and Ignatovic (1988), shedding of endogenous ALV did not occur in studies involving chicks that were experimentally infected with endogenous ALV. However, infection and shedding of endogenous ALV was found to occur commonly in meat-type chickens, but not in egglaying chickens (Ignatovic, 1986;Spencer & Chambers, 1992). In contrast, we found endogenous ALV in egg-laying chickens from two different commercial chicken stocks.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In additional case studies of Smith (1987) and Ignatovic (1988), shedding of endogenous ALV did not occur in studies involving chicks that were experimentally infected with endogenous ALV. However, infection and shedding of endogenous ALV was found to occur commonly in meat-type chickens, but not in egglaying chickens (Ignatovic, 1986;Spencer & Chambers, 1992). In contrast, we found endogenous ALV in egg-laying chickens from two different commercial chicken stocks.…”
Section: Discussioncontrasting
confidence: 45%
“…We expected the RT-PCR to detect subgroup A ALV because the prevalence of subgroup A ALV infections in chickens is higher than subgroup B ALV, while infections of subgroup C ALV and subgroup D ALV in chickens have only been reported in Finland (Sandelin & Estola, 1973;Calnek et al, 1991). However, subgroup E avian leukosis virus was not expected in commercial chicken eggs because infections of endogenous ALV usually do not result in detectable levels of GSA in egg albumen of egg-laying stocks (Spencer & Chambers, 1992). In this investigation, nucleotide sequence analysis performed on randomly selected RT-PCR products of albumen from eggs obtained from two different sources, White Leghorn chickens and retail stores, showed four of six samples were positive for endogenous ALV, while two of six samples were positive for exogenous ALV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gs antigen in albumen can also result from expression of endogenous viral (ev) genes, and high levels of the antigen have been found in eggs from meat-type chickens that were negative for exogenous virus (Ignjatovic, 1986;Spencer & Chambers, 1992). Sabour et al (1992) reported that meat chickens carry more of these ev genes than do egg-type stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Again, it was observed that second-generation samples of SML and SDL had higher OD values than ® rst generation samples, indicating the presence of exogenous virus shedding. It has been established that testing for the gs antigen shedding can bene® t an ALV-eradication programme, as most chickens that were viraemic with exogenous ALV had high levels of gs antigen shedding in eggs (Spencer & Chamber, 1992).…”
Section: Distribution Of Resistance a R Genementioning
confidence: 99%